2020
DOI: 10.1055/a-1289-1102
|View full text |Cite
|
Sign up to set email alerts
|

Medial Hoffa Fracture: Description of a Novel Classification System and Rationale for Treatment Based on Fragment-Specific Fixation Strategy

Abstract: Purpose This study aims to present a novel classification system and a rationale for treatment of medial Hoffa fractures. Methods We developed a simple comprehensive classification system for medial Hoffa fractures based on the fragment size and presence of fracture comminution. Furthermore, we propose a treatment algorithm based on two pillars: our case series of nine patients presenting medial Hoffa fractures and the best evidence-based pertinent literature. Fracture healing, range of motion, funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…As above mentioned, lateral Busch-Hoffa fractures present different morphology and characteristics from medial fractures. Therefore, Pires et al [ 17 ] proposed a new classification system especially developed for coronal plane fractures of the medial condyle, based on the size of the fractured fragment and the presence of comminution (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As above mentioned, lateral Busch-Hoffa fractures present different morphology and characteristics from medial fractures. Therefore, Pires et al [ 17 ] proposed a new classification system especially developed for coronal plane fractures of the medial condyle, based on the size of the fractured fragment and the presence of comminution (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[16] Figure 2 illustrates the types of fracture according to the Letenneur classification. Pires et al [17] proposed a modification to the original Letenneur classification, adding a variant pattern characterized by the presence of a type I fracture associated with a comminution zone or an intercalary fragment, which produces joint depression in the weight bearing zone of the femoral condyle. This modification of the original classification is supported by the mapping study of 74 distal fractures of the femur in the coronal plane carried out by Xie et al [5] The authors reported that central comminution (intercalary fragment) was present in 44.9% of coronal fractures of the lateral condyle.…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the lateral parapatellar approach requires a hyperflexed knee position for an optimal visualization of the articular surface and anatomic fracture reduction [7,23], although knee extension might facilitate the reduction due to ligamentotaxis by both anterior cruciate and lateral collateral ligaments. Additionally, this approach hinders placement of an augmenting plate osteosynthesis, whereas posterolateral approaches provide the necessary trajectory for crossed PA screws and also enable augmentation by a posterior buttress or lateral plates [14,26,27]. In contrast, smaller Hoffa fragments can only be sufficiently addressed with crossed PA screws, so that posterolateral approaches might be advantageous in the surgical treatment of Letenneur type II fractures [25].…”
Section: Ap Screw Fixation P a Screw Fixationmentioning
confidence: 99%